Design and implementation home security system and monitoring by using wireless sensor networks WSN/internet of thing IOT - Qasim Alsaid Noor, Hamzah Hadi (2018)
The proposed project is a protection of home security and can be monitored from anywhere in the world. Usually, we read on social media included newspapers regarding the theft and robbery cases at houses almost daily. This is also based on [[Numbeo website]] that provide a database to user every day about house robbery and theft cases. Not only that, accident such as cases of burning due to high temperatures or low humidity which cause the short circuit is increasingly happen too. These cases are one of the most serious problems that occur not only Malaysia, but other countries. It is not regarding the old cases happened, nowadays this accident increasing rapidly and frighteningly. Especially those who own money and jeweler at home to support their living expenses. Therefore, these problems must be solved and reduced by protecting the home by introducing technology for this purpose. Here, the idea of security of the home came to the design of home security system, which reduce the level of theft and alerts the user in case of emergency by sending a SMS when the users enter incorrect password in three times in row to the main door of the house or by using the RFID card that not registered in the system. In addition, the system also can detect gases that may cause death such as CO2 and etc. The installed sensors and controllers able to detect these gases and give alarm when they are inside the area and monitor them inside out by serial monitor window [[under idea internet of thing (IOT)]]. On the other hand, the system design to detect people entering the house using the human sensors (PIR) where the camera moving directly by servo motor to the detected area and take image. The user can access the images from anywhere in the world via [[Team Viewer.]]